Utilization of Agricultural Technology as Contextual Media in Science Learning on Sustainability and Agricultural Economics - Imanuel Rano Montolalu; Shapely S. Ambalao (Jurnal Penelitian Pendidikan IPA, 2025)
The agricultural sector faces challenges related to efficiency and sustainability, which can be explored in science learning to improve students' understanding of sustainability and economic concepts. Digitalization and modern agricultural technology offer a relevant context for science learning. This study examines the development of technology and digitalization in the agricultural sector, analyzes its potential as a contextual medium in science learning, and identifies challenges and opportunities for its implementation in education. The research method used is a systematic literature review by collecting data from various academic sources. The results of the study indicate that technologies such as the Internet of Things (IoT), automatic irrigation systems, and mobile-based applications can be used to teach science concepts such as ecosystems, energy, and environmental change in the context of agriculture. However, pedagogical strategies are needed to integrate these technologies effectively into the science curriculum. This study concludes that agricultural technology has great potential as a contextual medium in science learning, which is relevant to sustainability and agricultural economics, but requires further development in its educational approach